Unidirectional and bidirectional coupling of surface plasmons based on nonperiodic nano slit array - Udupi, Aparna; Handigod, Mruthyunjaya Somasekhara; Kumar, Sathish Madhava (Photonics Letters of Poland, 2018)
A 2D structure made up of nano slits to couple free space mode of any given wave front to a propagating Surface Plasmon Polariton (SPP) mode of Metal Insulator Metal (MIM) waveguide is proposed. The structure can be designed to act as either a unidirectional coupler or a bidirectional coupler. Designed structures are simulated using FEM technique and results for circular and plane wave fronts are demonstrated. From the results obtained, it is observed that there is an optimum aperture size for coupling maximum power into the MIM waveguide for the case of circular wave front. Full Text: PDF References Maier S A, Plasmonics: fundamentals and applications (Springer, Berlin 2007). CrossRef Chen J et al.,"Efficient unidirectional generation of surface plasmon polaritons with asymmetric single-nanoslit", Appl. Phys. Lett. 97, 4 (2010) CrossRef Yang X et al., "Unidirectional generation of surface plasmon polaritons by a single right-angled trapezoid metallic nanoslit", J. Phys. D: Appl. Phys., 50, 4 (2017). CrossRef Lu F et al. "An efficient and ultra-broadband unidirectional optical coupler for wide incidence angles", Opt. Commun., 379 (2016). CrossRef Liu D et al., "New RLL Decoding Algorithm for Multiple Candidates in Visible Light Communication", IEEE Photon. Technol. Lett., 27, 15 (2015). CrossRef Wang C M et al., "Angle-Independent Infrared Filter Assisted by Localized Surface Plasmon Polariton", IEEE Photon. Technol. Lett., 20, 13 (2008). CrossRef Wang C M, Feng D Y, "Omnidirectional thermal emitter based on plasmonic nanoantenna arrays", Opt. Express 22, 2 (2014). CrossRef Huang Y, Min C and Veronis G, "Light trapping by backside diffraction gratings in silicon solar cells revisited", Opt. Express 20, 20 (2012). CrossRef Liang X et al., "Undirectional launcher of surface plasmon polaritons based on subwavelength slits with side-illumination and backside-illumination", Optik 127, 3 (2016). CrossRef Dionne J A, Lezec H J and Atwater H A, "Highly Confined Photon Transport in Subwavelength Metallic Slot Waveguides", Nano letters 6, 9 (2006). CrossRef Ghatak, A., & Thyagarajan, K, An introduction to fiber optics Cambridge university press 1998). CrossRef Vial A et al., "Improved analytical fit of gold dispersion: Application to the modeling of extinction spectra with a finite-difference time-domain method", Phys. Rev. B: Condens. Matter, 71, 8 (2005). CrossRef